A Expressão “Em Cristo” e a Unidade da Igreja na Carta aos Efésios - Jung, Marcelo (Vox Scripturae - Revista Teológica Internacional, 2011)
This article is an essay about an approximation to the theme of the Church Unity through the analysis of the expression in Christ (ἐν Χριστῷ) (and similar and parallel expressions) in the Letter to the Ephesians. It´s observed that the expression in Christ is used in Ephesians to describe the person and the work of Christ, and also to describe the sphere created by him in his salvific work, the Church. Therefore, it´s a link between the Christology and the Eclesiology. The author observes the occurrence of the expression in Christ and analyses the ideas that are constructed from and around the same and search to establish relations of this content with the theme of the Church Unity. Arriving at the conclusion that the Church Unity, in Christ, is a mystical, universal and equalitarian, cosmic, free and inclusive/exclusive unity.
Keywords: Church Unity; Expression in Christ; Christology; Ecclesiology